Klasifikasi dan Identifikasi Topeng Sandur Manduro dari Grup “Gaya Rukun” di Desa Manduro Kabupaten Jombang - Dyva Agnecia; Lilik Indrawati; Agnisa Maulani Wisesa (Universitas Negeri Malang, 2021)
Abstract: Sandur Manduro is a performing art in the form of a traditional theater which includes music, dance, fine arts, theater, and literature. Research on the Sandur Manduro Mask art from the